In New Geon Extra Peritioneal Caesarean Section An Observational Study (Bangladesh Medical Journal, 2019)
This study was designed to find out the maternal and perinatal outcome among 80 women undergoing extraperitoneal cesarean section. This observational study was conducted at Institute of Child and Mother Health, Matuail, Dhaka from 1st March 2013 to 28th February 2014. Data were collected by structured questionaire ith the writen consent of patients irrespective of routine and emergency cases where the procedure was successful in all patients. During operation, time was taken from open to close, incision to delivery of baby, total amount of blood loss during procedure, intraoperative complications, APGAR score of newborn were documented. Time required for return of bowel sound mobilization of patient within 24 hour and, duration of hospital stay were also included. Success rate of extra peritoneal CS was 100%, Time taken from incision to delivery was ≤6 minutes in 62.2% cases, time taken from incision to closure was between 31-45 min in 72.5% cases, blood loss ≤500 ml in 62% cases, return of bowel function between 5-8 hours in 52.5%, mobilization within 24 hours in 52.5%, neonatal one minute APGAR score ≥7 in 93.91%.  As a surgical form of infection prophylaxis extraperitoneal cesarean section can be applied to avoid serious post-operative pelvic infections and its complications Extraperitoneal cesarean section would be a rational practice of cesarean section in the modern era.Bangladesh Med J. 2017 Sep; 46 (3): 94-96